2023
DOI: 10.1186/s12877-023-03737-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between walking and square dancing-oriented leisure-time physical activity and cognitive function among middle-aged and elderly people in Southwest China

Abstract: Background Southwest China is facing a serious aging problem across the country, but the status of cognitive function in middle-aged and elderly people in this region is superior to the national average. This study intends to reveal the leisure-time physical activity (LTPA) pattern in this region and explore whether this pattern is beneficial for cognitive function. Methods The data came from the 2019–2021 baseline survey on cognitive function of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Diagnoses of dementia and mild to severe cognitive impairment have been reported as predictors of PF decline. 12,15 In addition, "not vocalizing reciprocal exchanges at will" and always "waking at midnight" were predictors of PF decline. Falls, which are often directly related to PF decline, are more likely to occur at night, 26 primarily owing to insufficient lighting and a limited number of nursing home staff.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Diagnoses of dementia and mild to severe cognitive impairment have been reported as predictors of PF decline. 12,15 In addition, "not vocalizing reciprocal exchanges at will" and always "waking at midnight" were predictors of PF decline. Falls, which are often directly related to PF decline, are more likely to occur at night, 26 primarily owing to insufficient lighting and a limited number of nursing home staff.…”
Section: Discussionmentioning
confidence: 97%
“…Among all participants, several cognitive impairment indicators were significantly associated with functional decline. Diagnoses of dementia and mild to severe cognitive impairment have been reported as predictors of PF decline 12,15 . In addition, “not vocalizing reciprocal exchanges at will” and always “waking at midnight” were predictors of PF decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Square dancing is an excellent way to get women to exercise, especially in rural areas, where finding other exercise methods can be challenging. Additionally, square dancing has been shown to have social and mental health benefits, which can further contribute to its popularity among women ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many older adults in China prefer practicing Tai Chi in parks in the mornings and taking part in square dancing activities in community squares after dinner. The Li et al study showed that recreational sports with the same intensity as square dancing and walking had an improving effect on the cognitive performance of older adults [ 16 ].…”
Section: Introductionmentioning
confidence: 99%